2015
DOI: 10.1186/s12881-015-0167-0
|View full text |Cite
|
Sign up to set email alerts
|

A study in Polish patients with cardiomyopathy emphasizes pathogenicity of phospholamban (PLN) mutations at amino acid position 9 and low penetrance of heterozygous null PLN mutations

Abstract: BackgroundIn humans mutations in the PLN gene, encoding phospholamban - a regulator of sarcoplasmic reticulum calcium ATPase (SERCA), cause cardiomyopathy with prevalence depending on the population. Our purpose was to identify PLN mutations in Polish cardiomyopathy patients.MethodsWe studied 161 unrelated subjects referred for genetic testing for cardiomyopathies: 135 with dilated cardiomyopathy, 22 with hypertrophic cardiomyopathy and 4 with other cardiomyopathies. In 23 subjects multiple genes were sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…Several studies have identified CNVs as causative of cardiac diseases associated with SCD [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, exhaustive analysis of multiple genes in large cohorts of patients has never been performed for most SCD-related diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified CNVs as causative of cardiac diseases associated with SCD [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, exhaustive analysis of multiple genes in large cohorts of patients has never been performed for most SCD-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, several authors consider a CNV any imbalance larger than 50 base pairs [3] (bp) (this latter criterion is the one followed in the present work). Evidence supporting a role of CNVs in SCD-related pathologies has been reported, but robust studies with large cohorts of patients and multiple genes being screened have only been performed for specific SCD-related diseases [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only single reports describing genetic causes of HCM in Polish patients have been reported. [13][14][15] Therefore, the aim of the current study was to assess the genetic background of HCM in a cohort of patients from the south--eastern part of Poland, analyzed by an NGS panel including 404 genes known to harbor alterations affecting cardiovascular system function. Thanks to this approach, we could identify a MYB-PC3 truncating alteration that could represent a novel Polish founder MYBPC3 pathogenic variant.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…Similarly, individuals from the Netherlands with the R14del founder mutation have a severe phenotype 100 . However, other reports suggest a milder phenotype 101, 102 . Identifying the same primary mutation(s) with a range of phenotype dependent on genetic background supports that other factors, including genetic factors, may modify the outcome of DCM due to PLN mutations.…”
Section: Dcm Geneticsmentioning
confidence: 85%